Promoting mental, emotional, and social health : a whole school approach - Weare, Katherine, 1950- (Routledge, 2002)
Schools are now seen as being one of the key agents which can help redress society's most fundamental problems, create more cohesive communities and promote citizenship and a sense of social conscience in the young. Promoting Mental, Emotional and Social Health: A Whole School Approach provides a clear and practical overview of ways in which mainstream schools can promote the health of all those who work and learn in them. Supported by the latest new evidence from the UK and Europe as well as findings from the USA, it outlines and examines:* evidence that social and emotional learning and academic achievement can go hand in hand and that the same key factors underlie both happy and effective schools* the areas of school life that are the key to promoting social and affective health, including relationships with families and the community, management and the curriculum* the competencies that we all need to become more emotionally literate and relate to more effectively.